2017
DOI: 10.3892/etm.2017.4374
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the µ-opioid receptor and its related signaling pathways in the pathogenesis of premenstrual syndrome liver-qi stagnation

Abstract: Abstract. The present study aimed to investigate the roles of the µ-opioid receptor (MOR) and its related signaling pathways in the pathogenesis of premenstrual syndrome (PMS) liver-qi stagnation, along with the therapeutic effects of the Shu-Yu capsule in treating the condition. A PMS liver-qi stagnation rat model was established using a chronic restraint stress method. The protein expression level of MOR within rat hippocampal tissue was detected via western blot analysis and cyclic adenosine monophosphate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…With some modifications, the models were established as previously reported [16, 23]. The protocol for the LQS model was as follows: restraint stress was induced by placing mice individually in a ventilated 50 mL polypropylene tube (diameter of 3 cm and length of 10 cm, with a 1 cm hole in the cover for air diffusion) for 3 h every day for 28 days [24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With some modifications, the models were established as previously reported [16, 23]. The protocol for the LQS model was as follows: restraint stress was induced by placing mice individually in a ventilated 50 mL polypropylene tube (diameter of 3 cm and length of 10 cm, with a 1 cm hole in the cover for air diffusion) for 3 h every day for 28 days [24].…”
Section: Methodsmentioning
confidence: 99%
“…Although abundant studies have reported the effects of CSS on depression, rodent models of chronic mild stress or unavoidable punishment (learned helplessness) have been adopted for inducing depressive symptoms [15]. According to the theory of traditional Chinese medicine (TCM), depression includes different syndromes, such as Liver-Qi Stagnation (LQS), a syndrome induced by abnormal flow of the liver qi, which is characterized by depression, chest tightness and sighing [16], and liver stagnation and spleen deficiency (LSSD), which includes poor digestion, weight loss, diarrhoea, a bad appetite, and so on [17]; these are the two main depressive syndromes, and each has its own specific symptoms. CSS is uniquely used to treat LQS.…”
Section: Introductionmentioning
confidence: 99%
“…Paeoniflorin can significantly inhibit the intracellular Ca 2+ concentration and Cav1.2 increase in current density induced by KCl. In addition, it showed beneficial effects against affective disorders by regulating Cav1.2 through the CaM/CaMKII pathway ( Song and Xue, 2017 ). The abovementioned results further verified the correctness of the analysis results of the intersection targets of Chinese medicines and diseases in this study and clarified the Chinese medicine’s target and pharmacological mechanisms used in the treatment of PMS/PMDD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BDNF levels are reduced from the follicular to luteal phase. In a PMS rat model, BDNF expression is significantly decreased with the activation of opioid receptors ( 157 ). These inconsistent results may indicate distinct neuromodulator response alternations between PMS and PMDD.…”
Section: Melatonin Modulates Brain Gaba and Bdnfmentioning
confidence: 99%